An Arabidopsis tissue-specific RNAi method for studying genes essential to mitosis. - Brunilís Burgos-Rivera (Public Library of Science (PLoS), 2012)
A large fraction of the genes in plants can be considered essential in the sense that when absent the plant fails to develop past the first few cell divisions. The fact that angiosperms pass through a haploid gametophyte stage can make it challenging to propagate such mutants even in the heterozygous condition. Here we describe a tissue-specific RNAi method that allows us to visualize cell division phenotypes in petals, which are large dispensable organs. Portions of the APETALA (AP3) and PISTILLATA (PI) promoters confer early petal-specific expression. We show that when either promoter is used to drive the expression of a beta-glucuronidase (GUS) RNAi transgene in plants uniformly expressing GUS, GUS expression is knocked down specifically in petals. We further tested the system by targeting the essential kinetochore protein CENPC and two different components of the Spindle Assembly Checkpoint (MAD2 and BUBR1). Plant lines expressing petal-specific RNAi hairpins targeting these genes exhibited an array of petal phenotypes. Cytological analyses of the affected flower buds confirmed that CENPC knockdown causes cell cycle arrest but provided no evidence that either MAD2 or BUBR1 are required for mitosis (although both genes are required for petal growth by this assay). A key benefit of the petal-specific RNAi method is that the phenotypes are not expressed in the lineages leading to germ cells, and the phenotypes are faithfully transmitted for at least four generations despite their pronounced effects on growth.